What remains : a memoir of fate, friendship and love - Radziwell, Carole (New York Scribner, 2005)
The author traces her life and marriage to Anthony Radziwill, President Kennedy's nephew, in an account that describes her work as a journalist, her friendship with JFK, Jr., and his wife, and her husband's struggle with terminal cancer
B&T 2/06
Keywords: Radziwell, Carole -- Autobiography; Women Journalists -- Biography -- United States; Kennedy family -- Biography